Exploratory Sequential Study in the Implementation of Moodle-Based Flipped Classroom on Microteaching Class - Hasanah, Fatmawati Nur (AT-TA'LIM, 2023)
The Covid-19 pandemic has had a significant impact on the process of teaching and learning activities, one of which is social distancing. The flipped classroom learning method is a solution. The research objectives are: Knowing the process of implementing a moodle-based flipped classroom on microteaching class, Testing and describing the effect of implementing a moodle-based flipped classroom on microteaching on student achievement at IAIN Pekalongan, and Knowing student responses to the implementation of flipped classroom-based moodle. This research approach is mixed methods research. The sampling technique used in this research is purposive sampling. The results showed: 1) The implementation of the Moodle-based flipped classroom was carried out in several steps including: a) Making video tutorials about microteaching, b) Uploading videos on LMS moodle, c) Giving assignments, and d) When in class, the lecturer focuses on deepening the results of student assignments; 2) The effect of the flipped classroom implementation based on moodle based on the results of the t test that the calculated T value = [-44,338] or 44,338 and the significance value (2-tailed) is 0.000. So, there is an effect of the implementation of the Moodle-based flipped classroom in the microteaching class on student achievement at IAIN Pekalongan; 3) Student responses to: a) Microteaching class is included in the very positive category with an average of 89.17%, b) LMS moodle is included in the positive category with an average student response of 81.14%, and c) flipped classroom included in the positive category with an average student response of 83.70%.